Examination of the Impact of Large-Format Printing on Graphic Design Practice in 21st Century Nigeria - Akintola David Abiodun; Kalilu, Razaq Olatunde Rom (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The emergence of Large-Format Printing (LFP) technology has transformed global visual communication by enabling the production of large-scale, high-quality printed materials, significantly influencing Nigeria’s graphic design industry. This study aims to examine the impact of LFP on graphic design practice (GDP) in 21st-century Nigeria and propose strategies for sustainable development while addressing emerging challenges. A mixed-method approach was employed, with a primary qualitative focus through interviews and participant observation, supported by quantitative data collected using a Likert-scale questionnaire to assess designers’ perceptions of LFP’s influence. The findings reveal a dual impact. On the positive side, LFP has enhanced design scale, print quality, creative flexibility, and production efficiency, effectively overcoming the limitations of earlier methods such as letterpress printing, manual clamp offset printing, and hand-painted signboards. However, several challenges persist, including the oversaturation of practitioners, increased design piracy, and issues of color inconsistency, which undermine quality outcomes. These challenges highlight gaps in professional standards and regulation within the industry. The study concludes that while LFP has driven innovation and growth in Nigeria’s graphic design sector, its optimal benefits are constrained by the proliferation of unaccredited freelance designers. Therefore, the study recommends the implementation of targeted training programs and stricter professional accreditation systems through relevant regulatory bodies to ensure sustainable development and maximize the transformative potential of LFP technology.